2021
DOI: 10.4038/rjs.v12i2.106
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution affects lichen species richness, species density, relative growth form abundance and their secondary metabolite production: a case study in Kandy district, Sri Lanka

Abstract: Lichens are symbiotic associations between fungi and algae and/or cyanobacteria, consisting of three forms, viz: fruticose, foliose and crustose. Air pollution affects lichen diversity, percent cover, and density. The current study mainly compared the lichen species richness, density and relative abundance of each growth form among three selected sites with different degrees of pollution, viz: a site located in the Kandy City (S1), a site located 11 km away from the city (S2) and a site within a forest patch l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Since CRP and CRV have similar altitudinal gradients, the lower percentages of foliose species found in CRV than in CRP could be related to the intrinsic environmental heterogeneity of each basin (Körner and Spehn, 2002). However, since species diversity and growth form (crustose, foliose, and fruticose) are affected by atmospheric pollution (Gunawardana et al, 2021), the low proportion of foliose species found in CRV could be related to the open-pit mining activity of Bajo de la Alumbrera.…”
Section: Discussionmentioning
confidence: 99%
“…Since CRP and CRV have similar altitudinal gradients, the lower percentages of foliose species found in CRV than in CRP could be related to the intrinsic environmental heterogeneity of each basin (Körner and Spehn, 2002). However, since species diversity and growth form (crustose, foliose, and fruticose) are affected by atmospheric pollution (Gunawardana et al, 2021), the low proportion of foliose species found in CRV could be related to the open-pit mining activity of Bajo de la Alumbrera.…”
Section: Discussionmentioning
confidence: 99%